Nitrite and nitric oxide are important in the adjustment of primary metabolism during the hypersensitive response in tobacco - Mur, Luis A J (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.